2016
DOI: 10.4178/epih.e2016049
|View full text |Cite
|
Sign up to set email alerts
|

Survival and predictors of mortality among HIV patients on anti-retroviral treatment at Jinka hospital, South Omo, Ethiopia

Abstract: OBJECTIVESThe survival rate of human immunodeficiency virus (HIV)-infected patients receiving treatment in Ethiopia is poorly understood. This study aimed to determine the survival rate and predictors of mortality among HIV-infected adults on antiretroviral therapy (ART) at Jinka Hospital, South Omo, Ethiopia.METHODSA 6-year retrospective cohort study was conducted using 350 patient records drawn from 1,899 patients on ART at Jinka Hospital from September 2010 to August 2015. The data were analyzed using Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
19
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 25 publications
10
19
3
Order By: Relevance
“…Mortality in the first year of follow-up in our study (60%) was consistent with findings of a study in South Omo, Ethiopia, where 62.9% of patients died in the first year after the onset of ART [11]. Other retrospective cohort studies in Northern and North-western parts of Ethiopia have also reported similar death figures, with between 56% and 59% of total individuals dying before completing the first year of treatment [21,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mortality in the first year of follow-up in our study (60%) was consistent with findings of a study in South Omo, Ethiopia, where 62.9% of patients died in the first year after the onset of ART [11]. Other retrospective cohort studies in Northern and North-western parts of Ethiopia have also reported similar death figures, with between 56% and 59% of total individuals dying before completing the first year of treatment [21,22].…”
Section: Discussionsupporting
confidence: 92%
“…Gender and migration have also been associated with the risk of dying in seropositive individuals in South Africa [4]. In Ethiopia, factors such as severe anemia, a history of co-infection with tuberculosis (TB), marital status, WHO stage, low CD4 counts, poor adherence to ART, substance use, and opportunistic infections, were also found to be important determinants of HIV/AIDS-related deaths [9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…However, even with the present differences in mortality rate, the clinical message remains significantly similar that, despite the use of ART, the mortality among HIV-positive patients is comparatively higher than the general population in both developed and developing countries with comparable timing of these deaths in most series [21, 22]. For instance, in one study from Ethiopia, where 10.0% of patients on ART died in 6 years of follow-up, it was found that 62.9% of the reported deaths occurred in the first year of ART [23], while in a study by Johannessen et al from Manyara, Tanzania, it was indicated that 72.7% of the reported deaths occurred within the first 12 months of ART initiation [20]. Similarly, in the index study, 67.4% of the deaths also occurred within the first year of ART, further underlying the observation that most of the deaths among HIV patients occur within the first year of ART initiation as a potential point of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…So, a better knowledge of determinant factors would allow closer follow-up and more targeted interventions for HIV infected patients, thus reduce excess mortality, alter morbidity and improve quality of life (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%